ANALISIS WILLINGNESS-TO-PAY PADA EKOWISATA TAMAN NASIONAL GUNUNG RINJANI - Pipin Noviati Sadikin; Sri Mulatsih; Bambang Pramudya Noorachmat; Hadi Susilo Arifin (Jurnal Analisis Kebijakan Kehutanan, 2017)
Mount Rinjani National Park (MNRP) in the West Nusa Tenggara Province, popular as one of ectourism destinations for both international and domestic tourist. The number of tourist increases every year. However, MRNP was facing various problems including forest destruction which then becomes critical degraded lands, watersheds damaged, decreased of river water, garbage found at every ecotourism area due to lack of awareness and concern on the ecotourism resources value. This study aimed to analyze the willingness to pay (WTP) for MRNP ecotourism and determine the factors that affect it. The method was using contingent valuation method (CVM) to determine the value of ecotourism WTP and regression to determine the influenced factors to the value of WTP. The results showed that the mean of WTP was US $54.13 for international tourist, with MRNP ecotourism economic value and estimated revenue from entrance ticket of US $1,208,790/ year or Rp 14.50 billion/ year. While the mean of WTP for domestic tourist was Rp 40,650 with MRNP ecotourism economic value and estimated revenue from entrance fee were Rp 883,202,550. Factors that influenced the WTP both international and domestic tourists were education, income, family members, active in environmental organizations and knowledge on ecotourism.